Students’ Mathematical Problem-Solving Ability in Mobile Learning with Microsoft Kaizala Application - Ana Setiani; Nenden Mutiara Sari; Hamidah Suryani Lukman; Ida Rahmawati (Universitas Ahmad Dahlan, 2022)
This research was motivated by the fact that the mathematical problem-solving ability of junior high school students during the Covid-19 pandemic in Indonesia was low. The strategy and approach used in learning mathematics are success factors in the mathematics learning process. One of the objectives of this research is to analyze the mathematical problem-solving ability of junior high school students using mobile learning with the Microsoft Kaizala application. The method used in this research is an experiment with a Pre-Experimental Design Research and One-Group Pretest-Posttest Design Research Design. The research was conducted at SMPN 50 Satap Oku, Ogan Komering Ulu Regency, South Sumatra Province. The results showed that the final mathematical problem-solving ability of students who received learning using mobile learning with the Microsoft Kaizala application was better than the students’ initial mathematical problem-solving ability and the average percentage of students’ mathematical problem-solving ability achievement after using the Microsoft Kaizala application was 85.16% (excellent). It means that the students’ problem-solving ability is getting better after using mobile learning with Microsoft Kaizala application.